AGILE GOVERNANCE AND INSTITUTIONAL RESILIENCE: AN EVALUATION OF ADAPTIVE POLICY THE SOCIAL AFFAIRS OFFICE OF EAST JAVA PROVINCE - Karlina Winaryanti; Ulul Albab; Ika Devi Pramudiana (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the implementation of agile governance and its contribution to strengthening institutional resilience in adaptive policy evaluation at the Regional Social Service of East Java Province. The research employs a qualitative approach with a case study design to explore governance dynamics and policy evaluation processes within a public institutional context. Data were collected through in-depth interviews, observation, and document analysis, and were examined using thematic analysis techniques. The findings indicate that agile governance principles are reflected in policy responsiveness, flexible coordination, cross-sector collaboration, and data-driven evaluation processes. Adaptive policy evaluation contributes significantly to enhancing anticipatory, adaptive, and transformative capacities as the core dimensions of institutional resilience. However, structural challenges such as limited human resource capacity and regulatory synchronization continue to affect the optimization of adaptive governance practices. The study concludes that the integration of agile governance and institutional resilience represents a strategic approach to improving social policy effectiveness in complex and uncertain environments. This research provides theoretical contributions to the development of adaptive public administration paradigms and practical implications for strengthening institutional capacity in the social service sector.